Application of microbiological assay to determine the potency of intravenous antibiotics (Stamford Journal of Microbiology, 2020)
Demonstration of equivalent amounts of active pharmaceutical ingredient is a basic requirement for intravenous generic drugs prior to administration. Physicochemical methods are often used to determine concentration of antibiotics in biological fluids. However, it does not permit direct quantification of potency of a desired antibiotic. This study demonstrates the application of a microbiological assay to determine the potency and concentration of commercially available pharmaceutical-grade antibiotics used for injections. Concentration-dependent variation of inhibitory effect of four commercial brands of cefuroxime and two of ciprofloxacin were observed against two reference bacteria (Escherichia coli DH5α and Escherichia coli ATCC 8739) on Mueller Hinton agar. Regression analysis was used to assess the in vitro equivalence of generic products sold by different retail companies in Dhaka city. A linear relationship was found between the concentration and response of the bacteria in regression analysis where anti-log of X-intercept and slope showed the concentration and potency, respectively. The study showed excellent results of linearity (r2≥0.89), precision (inter assay variation ≤10% for cefuroxime and ≤20% for ciprofloxacin), accuracy and specificity tests for both types of antibiotics. Pharmaceutical equivalence demonstrated by four cefuroxime and two ciprofloxacin samples showed no significantly distinguishable slopes (P > 0.78 and P > 0.44) and intercepts (P > 0.25 and P > 0.07), respectively. Estimated potency for cefuroxime was 91.1-100.0% and for ciprofloxacin was 68.1-100.0%. Microbiological assay was found to be convenient, rapid, cost-effective, precise and accurate in demonstrating pharmaceutical equivalence of antibiotics in different dosage forms. This technique can be used as an alternative method for testing generic antibiotics prior to their use in animal and human.Stamford Journal of Microbiology, Vol.10 (1) 2020: 25-29